The Hazards of Video Games for Adolescents - Fenno Asko (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This scientific journal article aims to examine the potential dangers and risks associated with video games among adolescents. The increasing popularity of video games has raised concerns regarding their impact on the psychological, social, and physical well-being of young individuals. Through a comprehensive review of existing literature, this article explores the potential negative effects of video games on adolescent behavior and development. The findings highlight the need for awareness, moderation, and parental involvement to mitigate the hazards of excessive gaming among teenagers